β-Alanine Plus Sodium Bicarbonate Co-Supplementation Does Not Decrease Neuromuscular Fatigue in Swimming - Ribeiro, Felipe A.; Bertucci, Danilo R. [UNESP]; Kalva-Filho, Carlos A. [UNESP]; DE ARRUDA, Tarine B.; Norberto, Matheus S.; Raspantini, Giovanni L.; DE FREITAS, Ellen C.; Zagatto, Alessandro M. [UNESP]; Papoti, Marcelo (International Journal of Exercise Science, L.L.C., 2024)
This study aimed to investigate the effects of chronic β-alanine (βA) plus acute sodium bicarbonate (SB) co-supplementation on neuromuscular fatigue during high-intensity intermittent efforts in swimming. Eleven regional and national competitive-level young swimmers performed a neuromuscular fatigue assessment before and immediately after two 20 × 25-m front crawl maximal efforts every 90 s, performed at pre-and post-4-week co-supplementation. Neuromuscular fatigue was evaluated by percutaneous electrical stimuli through the twitch interpolation technique on the triceps brachii and quadriceps femoris. Performance was defined by the mean time of the 20 efforts and blood samples to lactate concentrations were collected every four efforts. Participants supplemented 3.2–6.4 g∙day−1 of chronic βA or placebo (PL) during four weeks, and acute 0.3 g∙kg−1 of SB or PL 60 min before the second assessment (allowing βA+SB and PL+PL groups). No statistical changes were found in neuromuscular fatigue of triceps brachii. In the quadriceps femoris, a main effect of time was found in potentiated twitch delta values in pooled groups, showing a statistical increase of 19.01% after four weeks (Δ = 13.05 [0.35-25.75] N; p = 0.044), without time × group interactions. No statistical difference was found in the swimming performance. Blood lactate increased by 25.06% only in the βA+SB group (Δ = 6.40 [4.62-8.18] mM; pBonf < 0.001) after the supplementation period. In conclusion, 4-week βA and SB co-supplementation were not able to reduce neuromuscular fatigue levels and improve performance in high-intensity intermittent efforts, but statistically increased blood lactate levels.
Keywords: buffering capacity; Ergogenic aids; voluntary activation